Contested or established? A comparison of legislative powers across regimes. Issue 4 (19th May 2019) - Wilson, Matthew Charles; Woldense, Josef
ABSTRACT: In research on authoritarian institutions, legislatures are portrayed as capable of resolving dilemmas between the leader and opposition members. Nevertheless, repeated interactions between a leader and their ruling coalition can lead to both contested dictatorships, in which institutions constrain the leader, and established dictatorships, in which the leader exercises near-complete control. To date, however, no one has examined the patterns by which powers vary across legislatures in different settings and over time. Using data from the Varieties of Democracy Project on legislative powers between 1900 and 2017, we conceptualize changes in the powers afforded to the national congress to characterize the development of regimes in either direction. The study expounds on the content of legislatures across regimes and the ways in which they change, encouraging scholars to further consider the relationship between regime dynamics and legislative institutionalization.